A expressividade vocal na prática do canto operístico: estabelecendo relações entre prosódia emocional e seus reflexos na voz cantada - Campinas, Carla Carolina Souza Leite [UNESP] (2015)
Most singers, teachers and voice students agree that the expression of emotions is an important parameter in music. In speech, in order to express emotions, humans use a resource named emotional prosody, which refers to modulations in pitch, sound duration and intensity that occur as a consequence to the speaker's emotional state. At the same time it allows listeners to identify humor variations of the person that is communicating himself. In this manner, if in opera (hybrid of theatre and music) there is a character interacting with others, who experiences several emotional states and that expresses those emotions in different ways, the emotional prosody may also be applied to ópera. However, even recognizing the relevance of the expressions of emotions, many teachers and singers have been neglecting its study. The present research aims to dig deeper into the expressivity research, by establishing a relationship between emotional prosody and singing as well as its consequences to singing voice. Therefore the reason to undertake the present research is theneed to explore de issue of expression of emotions trough the emotional prosody in music and, more specifically in the singing voice. In this way, in the first chapter issues regarding the teaching of expression of emotions in music will be addressed. In the second chapter, we will try to establish the origins of the relationship between expression of emotions in speech and music, in order to, in the third chapter, investigate the resemblances and differences in the decoding process of acoustic cues of expression of emotions by the listeners. In the last chapter, as an attempt to determine the possible effects in the listeners perception of expression of emotions in different situations, we will propose observations about the listening-perceptive analysis of the aria 'Parto, parto' (La Clemenza di Tito, W. A. Mozart) based on answers ...